The Slovene short story in English translation: survey and considerations - Cooper, Henry R. (Filozofska fakulteta, Oddelek za slovenistiko, Center za slovenščino kot drugi/tuji jezik, 2024)
The Slovene short story in English translation is a small but important window through which the English-reading world can see Slovenia as it is imagined by some of its finest writers. Just since 1991 over 130 short stories have been published by more than three dozen Slovene authors, about a quarter of whom are women. The themes of most of these stories show Slovenia in a somewhat grim light, with tales of escape (through suicide, travel, fantasy, insanity), horror stories about family life (often detailing crimes against or by children), and explicit vivisections of male-female relationships abounding. Many of these stories lack any Slovene couleur locale the only characteristic that makes them Slovene is their language. The paper makes particular note of English translations done by Slovene authors themselves (specifically Branko Gradišnik, Evald Flisar, Uroš Kalčič, Maja Novak, and Andrej Skubic), and the liberties author-translators take when rendering their works in a new linguistic environment. It speculates a bit on the nature and future of what might be considered to be a new genre. Slovenska kratka pripovedna proza v angleških prevodih je majhno, vendar pomembno okno, skozi katerega lahko angleško beroči svet vidi Slovenijo, kakor si jo zamišljajo nekateri najboljši pisatelji. Samo od leta 1991 naprej je bilo objavljenih več kot 130 kratkih zgodb več kot treh ducatov avtorjev, med katerimi je četrtina žensk. Teme večine zgodb prikazujejo Slovenijo v precej mračni luči, s pripovedmi o begu (s pomočjo samomora, potovanja, domišljije, norosti), z grozljivimi zgodbami o družinskem življenju (pogoste so podrobnosti zločinov nad otroki ali z otroki kot storilci) ali pa v njih avtorji razvidno secirajo odnose med moškim in žensko. V mnogih zgodbah manjka vsakršna slovenska lokalna obarvanost edina značilnost, ki jih dela slovenske, je jezik. Razprava se posebej posveča angleškim prevodom, ki so jih napravili avtorji sami (zlasti Brako Gradišnik, Evald Flisar, Uroš Kalčič, Maja Novak in Andrej Skubic), ...